Synthesis and Antimicrobial Activity of Some New Quinoxaline Derivatives - Ram Gopal Singhal; Syed Riaz Hashim; Sanjay Kumar Deivedi; Dharmchand Prasad Singh (MDPI AG, 2010)
2-Chloro-3-methylquinoxaline was selected as a nucleus around which various molecular transformations were performed to obtain new compounds expected to possess optimized antimicrobial activity. As very little work regarding attachment of ether linkages replacing chlorine at C-2 has been reported, it was thought worthwhile to synthesize various quinoxaline derivatives by replacing the C2 chlorine with an ether linkage attached to a benzene ring possessing an aldehyde or a free amino group which can be further reacted with aromatic amines and aromatic aldehydes, respectively, to yield new Schiff bases containing quinoxaline moieties. Thus the compounds 4-(2-methylquinoxalinyloxy) benzaldehyde (4), 2-[4-(substituted-benziminomethyl)-phenoxy]-3-methyl quinoxalines 5a-e, 4-(2-methyl-quinoxaline-3-yloxy)benzamine (6) and 4-(2-methylquinoxalin-3-yloxy)-N-substituted benzylidine benzamines 7a-e were synthesized and tested for their antimicrobial activity. The structures of the compounds were confirmed on the basis of their elemental and spectral data.